Analisis Tindak Tutur Ekspresif dalam Novel Laut Bercerita Karya Leila S. Chudori - Nadia Alfi Hidayah; Ciara Friska Sudrajat; Vina Salma; Sri Maulidiya Ardiyanti; Dyah Prabaningrum; Asep Purwo Yudi Utomo; Rossi Galih Kesuma (Pusat Riset dan Inovasi Nasional, 2024)
One of the goals of speech in communication is an effort to achieve the desired results of the speaker with the speech partner, speech is not only in oral communication but also in written communication such as novels .The method used is qualitative because the analysis in it explains the meaning of the characters' dialogue. As well as the use of data analysis techniques that use qualitative descriptive. Expressive speech acts in the novel Laut Bercerita based on the results of data analysis found 6 expressive speech acts in the novel Laut Bercerita, namely criticizing, praising, complaining, saying thank you, blaming. Expressive speech is a speech act intended by the speaker so that the speech can be interpreted as an evaluation of the things mentioned in the speech and has several functions in it. By using expressive speech the author is able to give messages and meaning to the reader about what he wants to convey through dialogue.